Imperatorin suppresses proliferation and angiogenesis of human colon cancer cell by targeting HIF-1α via the mTOR/p70S6K/4E-BP1 and MAPK pathways. (5th May 2017) - Mi, Chunliu; Ma, Juan; Wang, Ke Si; Zuo, Hong Xiang; Wang, Zhe; Li, Ming Yue; Piao, Lian Xun; Xu, Guang Hua; Li, Xuezheng; Quan, Zhe Shan; Jin, Xuejun
Abstract: Ethnopharmacological relevance: Angelica dahurica is a commonly used traditional Chinese medicine to treat migraine headache, toothache and cancer. Imperatorin is an active natural furocoumarin component originating from Angelica dahurica and has been shown to exhibit multiple bioeffector functions, including anti-cancer activity. However, the mechanism by which imperatorin inhibits tumor growth is not fully understood. Aim of the study: The aim of this study was to investigate the effectiveness of imperatorin as a treatment of cancer and to identify the underlying mechanisms of its anticancer activity. Materials and methods: HCT116, HeLa, and Hep3B cells were used in this study. Major assays were promoter-reporter gene assay, MTT, western blot analysis, immunofluorescence assay, reverse transcription-PCR (RT-PCR), flow cytometric analysis, clonogenic assay, EdU labeling and immunofluorescence, xenografted assay, and VEGF ELISA. Results: We here demonstrated the effect of imperatorin on hypoxia-inducible factor-1 (HIF-1) activation. Imperatorin showed a potent inhibitory activity against HIF-1 activation induced by hypoxia in various human cancer cell lines. This compound markedly decreased the hypoxia-induced accumulation of HIF-1α protein dose-dependently, whereas it did not affect the expressions of HIF-1β and topoisomerase-I (Topo-I). Further analysis revealed that imperatorin inhibited HIF-1α protein synthesis, without affecting the expression level of HIF-1α mRNA or degradation of HIF-1α protein. Moreover, the phosphorylation levels of mammalian target of rapamycin (mTOR), ribosomal protein S6 kinase (p70S6K), eIF4E binding protein-1 (4E-BP1), eukaryotic initiation factor 4E (eIF4E), extracellular signal-regulated kinase-1/2 (ERK1/2), SAPK/JNK and p38 were significantly suppressed by imperatorin. Furthermore, imperatorin prevented hypoxia-induced expression of HIF-1 target genes and flow cytometric analysis indicated that imperatorin induced G1 phase arrest in human colon cancer cell (HCT116). We found that imperatorin administration inhibits tumor growth and blocks tumor angiogenesis in a xenograft tumor model. Conclusions: These results show that imperatorin inhibited HIF-1α protein synthesis by downregulating the mTOR/p70S6K/4E-BP1 and MAPK pathways. These conclusions suggest that imperatorin is an effective inhibitor of HIF-1 and provide new perspectives into the mechanism of its anticancer activity. Graphical abstract: